The watercolour sourcebook : 60 inspiring pictures to transfer and paint with full-size outlines - Harrison, Terry, 1951-; Kersey, Geoff; Tait, Wendy; Woolley, Peter, 1960- (Search Press Limited, 2022)
"Packed full of ideas to inspire your watercolour painting, The Watercolour Sourcebook features 60 gorgeous paintings of landscapes, flowers, woodlands and mountains, providing endless inspiration for artists of all levels. Each project comes with clear guidance on how to paint it, a full-size reproduction of the finished painting, and a drawn outline that you can transfer straight onto your watercolour paper -- so no need to make an initial drawing! With so many beautiful paintings to choose from, you will find yourself returning to this fabulous resource time and time again. This book includes projects by Geoff Kersey, Peter Woolley, Terry Harrison and Wendy Tait, originally published in the What to Paint series."--Page [4] of cover.